3D-QSAR and Molecular Docking Studies on Oxadiazole Substituted Benzimidazole Derivatives: Validation of Experimental Inhibitory Potencies Towards COX-2 - Asati, Vivek; Ghode, Piyush; Bajaj, Shalini; Jain, Sanmati K.; Bharti, Sanjay K. (Current Computer - Aided Drug Design, 2019)
Background: In past few decades, computational chemistry has seen significant advancements in design and development of novel therapeutics. Benzimidazole derivatives showed promising anti-inflammatory activity through the inhibition of COX-2 enzyme. Objective: The structural features necessary for COX-2 inhibitory activity for a series of oxadiazole substituted benzimidazoles were explored through 3D-QSAR, combinatorial library generation (Combi Lab) and molecular docking. Methods: 3D-QSAR (using kNN-MFA (SW-FB) and PLSR (GA) methods) and Combi Lab studies were performed by using VLife MDS Molecular Design Suite. The molecular docking study was performed by using AutoDockVina. Results: Significant QSAR models generated by PLSR exhibited r2 = 0.79, q2 = 0.68 and pred_r2 = 0. 84 values whereas kNN showed q2 = 0.71 and pred_r2 = 0.84. External validation of developed models by various parameters assures their reliability and predictive efficacy. A library of 72 compounds was generated by combinatorial technique in which 11 compounds (A1-A5 and B1-B6) showed better predicted biological activity than the most active compound 27 (pIC50 = 7.22) from the dataset. These compounds showed proximal interaction with amino acid residues like TYR355 and/or ARG120 on COX-2(PDB ID: 4RS0). Conclusion: The present work resulted in the design of more potent benzimidazoles as COX-2 inhibitors with good interaction as compared to reference ligand. The results of the study may be helpful in the development of novel COX-2 inhibitors for inflammatory disorders.
Keywords: k-nearest neighbor